Living arrangements and cognitive decline among the elderly in Europe - Stefano Mazzuco; Silvia Meggiolaro; Fausta Ongaro; Veronica Toffolutti (University of East Anglia, Health Economics Group (HEG), 2013)
Family resources may play an important role in the wellbeing of the elderly. In this paper, we examine the association between living arrangements and cognitive decline among people over 65 in nine European countries under the hypothesis that living with others (i.e. spouse or/and children) vis-à-vis living alone may have positive effects on maintaining cognitive functioning. To this end we used data from the first two waves of the Survey of Health, Ageing and Retirement in Europe (SHARE), which provides five indicators of cognitive functions: orientation, memory, recall, verbal fluency, and numeracy. Net of both the potential biases due to the selective attrition and the re-test effects, the evidence shows that the impact of living arrangement on cognitive decline depends on both the country and the type of cognitive examined.
Keywords: J12; J14; 330; Living arrangements; cognitive decline; co-residence; re-test effect